2020
DOI: 10.3390/su12051787
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Impact of Climate Change Policies on the Market for Forest Industrial Residues

Abstract: As part of the Pan-Canadian Framework (PCF) on Clean Growth and Climate Change, the Government of Canada (GoC) introduced carbon pricing and is in the process of developing a Clean Fuel (CF) Standard. Both policies are key elements of the PCF and aim to reduce greenhouse gas (GHG) emissions through the use of lower carbon fuels, including bioenergy. Carbon pricing and the CF Standard are expected to increase the demand for biomass feedstocks, possibly threatening feedstock availability for existing forest indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Vice versa, Sohngen et al [11] found that enhanced forest protection in Europe or North America could increase wood production in natural forests in other parts of the world. In addition, more recently, different studies on impacts of environmental policies have been carried out on a national level, e.g., in terms of harvest leakage from Norway [12] and China [13] to countries in the rest of the world, or in terms of domestic impacts on wood-processing sectors in Canada [14]. Ford et al [15] detected a prevalence of deforestation leakage into surrounding buffer zones stemming from the protected areas in 120 tropical and subtropical forest regions.…”
Section: Introductionmentioning
confidence: 99%
“…Vice versa, Sohngen et al [11] found that enhanced forest protection in Europe or North America could increase wood production in natural forests in other parts of the world. In addition, more recently, different studies on impacts of environmental policies have been carried out on a national level, e.g., in terms of harvest leakage from Norway [12] and China [13] to countries in the rest of the world, or in terms of domestic impacts on wood-processing sectors in Canada [14]. Ford et al [15] detected a prevalence of deforestation leakage into surrounding buffer zones stemming from the protected areas in 120 tropical and subtropical forest regions.…”
Section: Introductionmentioning
confidence: 99%
“…The wood processing industry is basically divided into downstream industry and upstream industry (Lin et al, 2020). The upstream industry includes the saw mill, plywood industry, particle board industry and MDF industry (Hope et al, 2020). Downstream industries consist of wood working, furniture and handicraft industries.…”
Section: Introductionmentioning
confidence: 99%